New insights into the reinforced reduction performance of Fe0/C internal electrolysis activated by persulfate for p-nitrophenol removal. (September 2020) - Xu, Zhihua; Gao, Yuquan; Sun, Zhenhua; Zhang, Daofang; Zhou, Yuwei; Chen, Weifang
Abstract: In this study, the reduction of iron-carbon internal electrolysis was reinforced by persulfate for p-nitrophenol removal. The effects of persulfate dosage, initial pH and iron-carbon mass ratio were comprehensively studied in batch experiments. In the system of iron-carbon internal electrolysis coupled with persulfate, the iron-carbon internal electrolysis and persulfate had a significant mutual influence, exhibiting a wide range of pH in the treatment process. Moreover, the coupled system also showed the remarkable removal and degradation efficiency of p-nitrophenol according to the contrast experiments. The satisfactory results should be attributed to the potential reduction of iron-carbon internal electrolysis, which was stimulated by persulfate to transform the nitro group to the amine group, accompanying the subsequent oxidation. Furthermore, persulfate possessed the ability that the dynamically destructive effect on external and internal of Fe 0 and the scavenging action on activated carbon, effectively strengthening the potential energy for release and transfer of reductive substances. Both HO and SO4 − as the main free radicals were formed to mineralize the intermediates in the coupled system. These findings indicate that the system of iron-carbon internal electrolysis coupled with persulfate can be a promising strategy for the treatment of the toxic and refractory wastewater. Graphical abstract: Image 1 Highlights: Relatively high removal and degradation efficiency of PNP gained in Fe 0 /C-PS system. Persistent activation and depassivation of Fe 0 in virtue of PS were revealed. Reduction as the vital reaction was significantly enhanced in Fe 0 /C-PS system. The capacity of adsorption and transfer electrons of GAC was enhanced.